Violation Of Properity As A Form Of Trade Secret Violation: Orientation And Construction - Suhardin, Yohanes; Khuan, Hendri; Suryadi, Asep; Ishwara, Ade Sathya Sanathana; Thuong, Mac Thi Hoai (Faculty of Law, Universitas Jenderal Soedirman, 2023)
Trade secret is one of the intellectual property that must be protected. This relates to the existence of a company whose economic activities are based on trade secrets. Problems related to trade secrets are trade secret violations which are only formulated as violations of positive law provisions. In fact, in the era of modern business development there is a potential for violations of trade secrets that have not been accommodated by positive law. This study aims to analyze as well as construct aspects of a violation of decency as a form of violation of trade secrets. This research is a normative legal research that uses a concept, case, and statutory approach. The results of the study confirm that the orientation of a violation of decency as a form of trade secret violation can be carried out through extensive interpretation related to expanding the meaning of